2008
DOI: 10.1080/13607860701797232
|View full text |Cite
|
Sign up to set email alerts
|

Movement in mind: The relationship of exercise with cognitive status for older adults in the Swedish National Study on Aging and Care (SNAC)

Abstract: The purpose of this study was to investigate the relationship of light and strenuous exercise, and self-reported change in exercise status, with different components of cognitive function, and gender differences in this relation, in a large, representative sample included in the Swedish National study on Aging and Care (SNAC). Eight-hundred-and-thirteen participants in age-cohorts from 60-96 years completed a wide range of cognitive function tests, the Mini Mental State Exam (MMSE) and survey questions concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
4
25
3
Order By: Relevance
“…This finding concurs with previous RCTs[8; 24; 25]. In contrast, subjective assessment of aerobic activity level is associated with greater benefits for global cognitive function as assessed by the MMSE[84; 85], as well as executive functions[85], in men compared to women. Importantly, our results extend previous work that showed improvements in executive functions after RT and MT interventions[28; 29; 30; 66; 68; 69; 71; 73; 76; 77; 78; 79; 81; 82], and show for the first time that these beneficial effects may be dependent on sex, as studies with a high percentage of women showed the largest effect sizes.…”
supporting
confidence: 91%
“…This finding concurs with previous RCTs[8; 24; 25]. In contrast, subjective assessment of aerobic activity level is associated with greater benefits for global cognitive function as assessed by the MMSE[84; 85], as well as executive functions[85], in men compared to women. Importantly, our results extend previous work that showed improvements in executive functions after RT and MT interventions[28; 29; 30; 66; 68; 69; 71; 73; 76; 77; 78; 79; 81; 82], and show for the first time that these beneficial effects may be dependent on sex, as studies with a high percentage of women showed the largest effect sizes.…”
supporting
confidence: 91%
“…The majority of the respondents were physically active every day, and it is well known that regular physical activity improves health 19,20,58. This result may explain the high score of self-care ability, good mental health, and life satisfaction in the current study as a whole, taking into account that the most vulnerable and sedentary people might be in the nonresponding group.…”
Section: Discussionmentioning
confidence: 69%
“…In a cohort of elderly Chinese participants, a lack of exercise at baseline was associated with a statistically significant twofold increase in the risk of cognitive impairment over a 36-month period in women only 48. Contrary to the above findings, in a cross-sectional analysis of self-reported level of physical activity, Lindwall et al 49 found that engaging in light exercise was associated with better executive functions and global cognition compared with never exercising in men, but this same relationship was not seen in women. The authors, however, note that the discrepancy in their results was likely due to the fact that the women who never exercised in their study scored higher on the cognitive tasks compared with the men who never exercised, indicating that there was more room for improvement in the men with increasing level of exercise.…”
Section: The Who and The How: Biological Sex Bdnf Genotype And Theimentioning
confidence: 74%